Pengaruh Biaya Kualitas Terhadap Minimalisasi Produk Rusak (Studi Kasus Pada Produk Home Industri Makanan) - Yuniastuti, Rina Milyati; Nasyaroeka, Jhon; Lestari, Fransiska Wahyu (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2024)
The research aims to analyze the effect of quality costs (prevention costs, assessment costs) on the damaged products. According to this research, a damaged product is a failed product; products that cannot be traded according to business standards. This research was carried out regarding to the issue of damaged products which could cause in losses due to product quality not being guaranteed, increasing of raw materials and increasing of production costs. This research object is a home industry business which making snacks called Risoles. This home industry business is included in the micro, small and medium enterprises. This research sample was taken from 2020-2022. The research method used descriptive quantitative analysis. Statistical tests used multiple regression analysis. Model feasibility test and t test and determination test. The F test shows the prevention costs and assessment costs affect damaged products. The t test/partial test result shows the prevention costs has an effect on damaged products, the assessment costs of also has an effect on damaged products. This research can make a contribution to home industry to more focus in minimizing damaged products so that they do not suffer losses and it is also recommended to make quality cost reports periodically.